Endometrial thickness as a biomarker for ongoing pregnancy in IUI for unexplained subfertility: a secondary analysis. Issue 1 (8th January 2020) - Danhof, N A; van Eekelen, R; Repping, S; Mol, B W J; van der Veen, F; van Wely, M; Mochtar, M H; ,
Abstract: STUDY QUESTION: What is, in couples with unexplained subfertility undergoing IUI, the impact of gonadotrophins compared to clomiphene citrate (CC) on endometrial thickness (EMT) in relation to ongoing pregnancy? SUMMARY ANSWER: In women with unexplained subfertility undergoing IUI with ovarian stimulation, gonadotrophins lead to a thicker endometrium compared to CC, but this does not affect ongoing pregnancy rates. WHAT IS KNOWN ALREADY: A systematic review and meta-analysis among couples with unexplained subfertility undergoing IUI with ovarian stimulation showed that women who conceived had, on average, a thicker endometrium than women who did not conceive, but this evidence is not robust due to a high level of heterogeneity. There was insufficient data to draw any conclusions on EMT and the effect on pregnancy outcomes. STUDY DESIGN, SIZE, DURATION: We performed a secondary analysis of a multicentre randomized controlled superiority trial in couples with unexplained subfertility undergoing IUI with adherence to strict cancellation criteria. In total, 738 couples recruited between July 2013 and March 2016 were allocated to ovarian stimulation with gonadotrophins ( n  = 369) or with CC ( n  = 369) for a maximum of four IUI cycles. According to local protocol, recombinant FSH, urinary FSH or hMG was used. Natural conceptions and cancelled cycles were removed from this secondary analysis, as they do not provide any information on pregnancy in relation to stimulation after IUI. Ongoing pregnancy was defined as a positive heartbeat at or beyond 12 weeks of gestation. PARTICIPANTS/MATERIALS, SETTING, METHODS: We first determined the difference in EMT between women randomized to gonadotrophins (75 IU) and CC (100 mg) over all cycles using a linear mixed model. We then investigated the association between EMT and ongoing pregnancy after IUI using a logistic regression model, adjusted for the allocated drug, number of dominant follicles, female age, BMI, duration of subfertility, primary or secondary subfertility, referral status, smoking status, cycle number and total motile sperm count. To conclude, we investigated the association between EMT and ongoing pregnancy by logistic regression separately in women allocated to gonadotrophins and in women allocated to CC. MAIN RESULTS AND THE ROLE OF CHANCE: A total of 666 couples underwent 1968 IUI cycles. Of these, 330 couples were allocated to gonadotrophins, of which 85 conceived leading to ongoing pregnancy (rate per cycle 8.9%) and 336 couples were allocated to CC, of which 71 conceived leading to ongoing pregnancy (rate per cycle 7.0%) (relative risk (RR) 1.22, 95% CI 0.92 to 1.61). The mean EMT was 8.9 mm (SD 2.1) in women treated with gonadotrophins and 7.5 mm (SD 2.1) in women treated with CC (adjusted mean difference 1.4 mm; 95% CI: 1.1–1.7). The overall mean EMT was 8.4 mm (SD 2.2) in women that conceived leading to ongoing pregnancy and 8.2 mm (SD 2.2) in women that did not conceive (adjusted odds ratio (OR): 1.03 per 1 mm increase, 95% CI 0.95–1.12). There was no association between EMT and ongoing pregnancy in women treated with gonadotrophins or CC (OR: 1.01 per 1 mm increase, 95% CI 0.90–1.13, and 1.10 per 1 mm increase, 95% CI 0.99–1.23, respectively). LIMITATIONS, REASON FOR CAUTION: Since this is a secondary analysis, the data should be interpreted prudently as secondary analyses are prone to false-positive findings or could be underpowered to show associations that the study is not primarily set up for. WIDER IMPLICATIONS OF THE FINDINGS: In women with unexplained subfertility and treated with IUI, gonadotrophins lead to a significantly thicker endometrium compared to CC, but there was no evidence of a consistent association between EMT in women treated with gonadotrophins or CC and the ongoing pregnancy rate. A relatively thin endometrium after CC is therefore not a valid reason to prefer gonadotrophins as the stimulation agent in IUI for unexplained subfertility. STUDY FUNDING/COMPETING INTEREST(S): The initial trial was funded by the Netherlands Organization for Health Research and Development (ZonMw) (Health Care Efficiency Research; project number: 80-83600-98-10 192). The EudraCT number for this trial was 2013-001034-18. Prof. Dr B.W.J.M. is supported by a NHMRC Practitioner Fellowship (GNT1082548). B.W.M. reports consultancy for Merck, ObsEva and Guerbet. The other authors declare no conflicts of interest. TRIAL REGISTRATION NUMBER: NTR 4057